Pharmacokinetic‐pharmacodynamic modelling of the anti‐FcRn monoclonal antibody rozanolixizumab: Translation from preclinical stages to the clinic. (23rd November 2021) - Lledo‐Garcia, Rocio; Dixon, Kate; Shock, Anthony; Oliver, Ruth
Abstract: Rozanolixizumab is a fully humanized high‐affinity anti‐human neonatal Fc receptor (FcRn) monoclonal antibody (mAb) that accelerates the removal of circulating immunoglobulin G (IgG), including pathogenic IgG autoantibodies, via the natural lysosomal degradation pathway. The aim of this study was to develop a pharmacokinetic/pharmacodynamic (PK/PD) model characterizing the effect of rozanolixizumab on IgG levels in cynomolgus monkeys, translate it into humans to support the first‐in‐human (FIH) rozanolixizumab clinical trial study design, and, ultimately, develop a PK/PD model in humans. Simulations from the preclinical model were performed to predict IgG responses in humans and select clinically relevant doses in the FIH study. Good alignment was observed between predicted and observed reductions in IgG, which increased with increasing dose in the FIH study. The model successfully described the PK of the 4 and 7 mg/kg intravenous (i.v.) dose groups, although the PKs were underpredicted for the 1 mg/kg i.v. dose group. Updating the model with subsequent human data identified parameters that deviated from preclinical assumptions. The updated PK/PD model was able to effectively characterize the PK FcRn‐IgG nonlinear system in response to rozanolixizumab in the FIH data.